Triple therapy in COPD: new evidence with the extrafine fixed combination of beclomethasone dipropionate, formoterol fumarate, and glycopyrronium bromide - Singh,D; Corradi,M; Spinola,M; Papi,A; Usmani,OS; Scuri,M; Petruzzelli,S; Vestbo,J (International Journal of Chronic Obstructive Pulmonary Disease, 2017)
The goals of COPD therapy are to prevent and control symptoms, reduce the frequency and severity of exacerbations, and improve exercise tolerance. The triple combination therapy of inhaled corticosteroids (ICSs), long-acting beta2 agonists (LABAs), and long-acting muscarinic antagonists (LAMAs) has become an option for maintenance treatment of COPD and as a “step-up” therapy from single or double combination treatments. There is evidence that triple combination ICS/LABA/LAMA with different inhalers improves lung function, symptoms, and health status and reduces exacerbations. A new triple fixed-dose combination of extrafine beclomethasone dipropionate (100 µg/puff)/formoterol fumarate (6 µg/puff)/glycopyrronium bromide (12.5 µg/puff) has been developed as a hydrofluoroalkane pressurized metered dose inhaler. Two large pivotal studies showed that this extrafine fixed ICS/LABA/LAMA triple combination is superior to fixed ICS/LABA combined therapy and also superior to the LAMA tiotropium in terms of lung function and exacerbation prevention in COPD patients at risk of exacerbation. This review considers the new information provided by these clinical trials of extrafine triple therapy and the implications for the clinical management of COPD patients.